On the agency of rivers. (26th November 2014) - Edgeworth, Matt
Abstract : Veronica Strang has written an excellent account of the fluid relationships between humans and the non-human materiality of water. The very idea of anthropology of water challenges our commonly held assumptions about water being just a material or economic resource (or, conversely, about anthropology being just the study of people). It holds that water is socially, politically and ritually constituted, while acknowledging at the same time that water also has an existence outside the human domain. There is much to agree with and to be inspired by in the paper, which is especially strong on 'fluidity and consistency at every level of human–non-human engagement' (p. 133). By virtue of the emphasis on that specific aspect, however, there are some aspects which are underemphasized, and it is these which I focus on in my comments.